The Benefits of Unemployment Insurance Fund in Jordan - Jihad A. Abu Al Sondos (European Scientific Journal, ESJ, 2019)
This paper focuses on identifying the benefits of the Unemployment Insurance Fund (UIF) in Jordan, and how it achieves a direct and indirect social protection for unemployed insured persons through enhancing job security, reducing unemployment rates, and encouraging graduates to recruit on jobs that are available in many different private sectors. The research employs a descriptive statistical method by analysing the collected annual data that is issued by the Social Security Corporation (SSC), which is related to a cumulated size of beneficiaries from the UIF and total compensation paid for insured persons within the same period. The data pertaining to these persons comprises of their distribution by gender, age, geographical area, wages, unemployment time, and economic activities. In this research, it is recommended to extend a number of beneficiaries from the UIF by including more unemployed persons who subscribe at the SSC, and who increase their ratio estimation of the monthly compensation. Additionally, the research enhances the corporative efforts by involving international, regional, and local organisations that aim at reducing unemployment rates by hosting an effective debate with all of them.